SITEM PERSIAPAN LAHAN DAN PEMBERIAN BAHAN ORGANIK PADA BUDIDAYA JAGUNG DI LAHAN KERING - Ridwan Ridwan; Yulinar Zubaidah (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2010)
Land preparation and organic matter application was chosen as an alternative to improve soil physical, chemical, and biological properties in increasing yield of maize. The field experiment was conducted in Koto Baru Simalanggang, Lima Puluh Kota Regency, West Sumatra, in the dry season 2007. The treatments consist of three types of land preparation ( no tillage, direct composting in the area, and strip tillage) and two levels of organic matter application ( 0 and 2 t/ha). Objectives of the experiment were to observe the effect of land preparation methods and organic matter application on growth and yield of maize in the upland area. Results of the experiment showed that, land preparation types did not give significant effect on all parameter observed. Application of organic matter 2 t/ha had increased cob length, number of seed per row, and yield of maize. Maize yield was about 6.07 t/ha without and 6.85 t/ha with organic matter application. Key Words : Land preparation System, Organic Matter Application, Maize , Upland Area.